Abiotic gradients drive floristic composition and structure of plant communities in the Monte Desert - Acebes, Pablo (2010)
Defining plant communities in desert zones is difficult due to large scale homogeneity and small scale heterogeneity, thus making provision of systematic information for conservation decisions problematic. We analysed plant communities of the most arid sector of Monte Desert for structure, plant composition and environmental variables. Small-scale variables such as slope, rock cover, bare ground and litter, as well as largescale ones such as species diversity, composition and similarity within and between sites were included. Analyses of floristic composition showed the difficulty of segregating distinct communities due to high internal heterogeneity and overlap between the different sites. Only mesquite woodlands, a community situated at the extreme of the soil moisture gradient was segregated. Ordination on structural variables was somewhat more successful in segregating communities on the basis of substrate type and of tree and shrub cover. Our results showed the difficulty distinguishing plant communities in temperate deserts, suggesting the existence of relatively stable assemblages of species at the extremes of the gradients and of great heterogeneity within and between sites. They cannot be defined by floristic variables solely, but require environmental information also.